New fixed links across the Öresund – what is the point? - Hansen, Sten (Proceedings from the Annual Transport Conference at Aalborg University, 2015)
During the last years, several investigations on new fixed links across the Öresund have been conducted and presented to the public. These new fixed links intend to supplement the already existing bridge between Malmö and Copenhagen, the Öresund Bridge. We review these proposals and outline their intended function in the regional cross-border transport system as well as the European transport system (TEN-T) in order to identify the objective(s) of the proposals. New fixed links are generally proposed as a “one-solution-only” alternative, focusing more on the proposed alternative, than identifying the transport problem. The overall aim of the paper is to achieve a deeper understanding of the basic transport-planning question: What is the problem? Based on a review of reports, we conclude that four key-objectives exist for a new fixed link across the Öresund. Each proposal meets one or more of these objectives.